Effective reduction of nitrophenols and colorimetric detection of Pb(ii) ions by Siraitia grosvenorii fruit extract capped gold nanoparticles. Issue 25 (26th April 2021) - Le, Van Thuan; Duong, Truong Giang; Le, Van Tan; Phan, Thanh Long; Huong Nguyen, Thi Lan; Chau, Tan Phat; Doan, Van-Dat
Abstract : Siraitia grosvenorii fruit extract capped AuNPs exhibited excellent catalytic activity in the reduction of nitrophenols and high sensitivity and selectivity for detection of Pb(ii ) ions. Abstract : This study presents a simple and green approach for the synthesis of Siraitia grosvenorii fruit extract capped gold nanoparticles (SG-AuNPs). The SG-AuNPs samples prepared under the optimized conditions were characterized by various techniques (UV-Vis, XRD, FTIR, HR-TEM, EDX, DLS). The biosynthesized nanoparticles were then studied for the reduction of 2-nitrophenol (2-NP) and 3-nitrophenols (3-NP) and for colorimetric detection of Pb 2+ ions. The characterization results revealed that the crystals of SG-AuNPs were spherical with an average size of 7.5 nm. The FTIR and DLS analyses proved the presence of the biomolecule layer around AuNPs, which played an important role in stabilizing the nanoparticles. The SG-AuNPs showed excellent catalytic activity in the reduction of 3-NP and 2-NP, achieving complete conversion within 14 min. The catalytic process was endothermic and followed pseudo-first-order kinetics. The activation energy was determined to be 10.64 and 26.53 kJ mol −1 for 2-NP and 3-NP, respectively. SG-AuNPs maintained high catalytic performance after five recycles. The fabricated material was also found to be highly sensitive and selective to Pb 2+ ions with the detection limit of 0.018 μM in a linear range of 0–1000 μM. The practicality of the material was validated through the analyses of Pb 2+ in mimic pond water samples. The developed nanoparticles could find tremendous applications in environmental monitoring.